TMIC-46. GLIOMA-INDUCED SYNAPTOGENESIS IS ENRICHED WITHIN FUNCTIONAL CONNECTIVITY NETWORK HUBS AND INFLUENCES LANGUAGE PROCESSING IN ADULT IDH WT GLIOBLASTOMA. (11th November 2019) - Krishna, Saritha; Kakaizada, Sofia; Valdivia, Claudia; Seo, Kyounghee; Raleigh, David; Findlay, Anne; Almeida, Nyle; Sudharshan, Rasika; Choudhury, Abrar; Brang, David; Nagarajan, Srikantan; Berger, Mitchel; et al.
Abstract: INTRODUCTION: Little is known about the mechanisms by which gliomas integrate into functional neural networks and influence complex cognitive processes such as language. Glioma-neuron interactions are bidirectional, with increased neuronal activity promoting tumor growth and the latter in turn influencing neuronal excitability and synaptic connections. It remains unknown whether glioma-neuron interactions play a role in maintaining long-range neural networks subserving cognition in humans. We test the hypothesis that glioma-neuron interactions ("synaptogenic glioma cells") are enriched within intratumoral high functional connectivity (FC) network hubs, thereby influencing language processing via release of synaptogenic factors into the tumor microenvironment. METHODS: We employed magnetoencephalography imaginary coherence measures to identify intratumoral high (HFC) and low (LFC) functional connectivity network hubs in newly diagnosed glioblastoma patients. Primary patient samples and cultures from HFC and LFC sites were assessed for pre and post-synaptic marker expression (IF), cocultured with murine hippocampal neurons, and induced neuron organoids. ECOG Field recordings were performed on HFC/LFC tumors. Secreted proteins were measured from patient serum and LFC/HFC culture supernatant. Language assessments were performed to correlate task performance with FC measures. RESULTS: Primary patient samples from HFC regions are enriched for glioblastoma cells with a synaptogenic profile as characterized by pre- and post-synaptic marker expression at both tissue and cellular level (coculture with mouse hippocampal neuron and organoid models). RNA sequencing and proteomic analyses from HFC samples revealed a neurogenic signature including thrombospondin 1 (TSP1). Overexpression of TSP1 in LFC primary patient cultures rescues the synaptogenic and proliferative phenotype. Importantly, we found a linear relationship between intratumoral HFC with patient serum TSP1 (ELISA) with a further correlation with language task performance. CONCLUSION: An enriched population of synaptogenic glioma cells are organized within intratumoral high network connectivity regions. Glioma-induced neuronal synaptogenesis contributes to the microenvironment in support of network connectivity through secretion of TSP1.